Structural, morphological, and optical properties of strontium doped lead-free BCZT ceramics. Issue 11 (1st June 2021) - Verma, Ritesh; Chauhan, Ankush; Batoo, Khalid Mujasam; Kumar, Rajesh; Hadi, Muhammad; Raslan, Emad H.
Abstract: We report the synthesis of Sr 2+ doped Ba0.9-x Ca0.1 Srx Ti0.8 Zr0.2 O3 nano-ceramics by the conventional solid-state reaction method. Phase formation of single-phase orthorhombic ABO3 type structure with space group P2mm was confirmed through X-ray diffraction (XRD). The crystallite size increased with increasing doping concentration from 25.46 nm to 52.96 nm as calculated by the Scherrer formula and from 47.1 nm to 88.5 nm by the Williamson-Hall method. The lattice parameter, dislocation density, and apparent density decreased with doping, except for when x = 0.05. The porosity was found to increase up to 16.8% with increasing doping. Field emission scanning electron microscopy (FESEM) shows that samples exhibit a flake-like structure. X-ray photoelectron spectroscopy (XPS) analysis confirms that Sr-ions occupy the Ca-site, for x = 0.05, and force the Ca ions to occupy the Ti-sites. For the higher concentration of Sr, i.e. x ≥ 0.15, no more forced substitution is observed and Sr-ions occupy the Ba-site only, which decreases oxygen vacancies. Diffused rings observed in selective area electron diffraction (SAED) patterns indicate the high crystalline order of the samples. The Fourier-transformed infrared spectroscopy (FTIR) measurements show a single broad peak between 544 and 594 cm −1 for all the compositions, while two prominent peaks are observed for the composition x = 0.05 at 528 cm −1 and 592 cm −1 . The Raman spectra show a shift in the most prominent peak, observed approximately 517 cm −1 .